2007
DOI: 10.1093/glycob/cwm051
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans in Hydra magnipapillata (Hydrozoa, Cnidaria): demonstration of chondroitin in the developing nematocyst, the sting organelle, and structural characterization of glycosaminoglycans

Abstract: The hydrozoan is the simplest organism whose movements are governed by the neuromuscular system, and its de novo morphogenesis can be easily induced by the removal of body parts. These features make the hydrozoan an excellent model for studying the regeneration of tissues in vivo, especially in the nervous system. Although glycosaminoglycans (GAGs) and proteoglycans (PGs) have been implicated in the signaling functions of various growth factors and play critical roles in the development of the central nervous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…The actual identification of the disaccharides depends on determining the retention time relative to authentic standards, which are sometimes difficult to procure. At times the profile can be confusing due to spurious peaks or contaminants (3)(4)(5).…”
mentioning
confidence: 99%
“…The actual identification of the disaccharides depends on determining the retention time relative to authentic standards, which are sometimes difficult to procure. At times the profile can be confusing due to spurious peaks or contaminants (3)(4)(5).…”
mentioning
confidence: 99%
“…GAGs are known to participate in many biological processes like signaling, cell adhesion, infection of pathogens, brain development, modulation of enzymes, cytokines, and growth factors (14,15). In a recent publication, Yamada et al (16) characterized GAGs in Hydra magnipapillata and demonstrated by immunostainings that the epitope of the anti-chondroitin antibody 473A12 is present in developing nematocysts, though the precise role of this nematocyst-specific chondroitin remained unclear. Here, we demonstrate that this chondroitin forms the outer layer of the developing nematocyst tubule, both in Hydra and the sea anemone Nematostella vectensis.…”
mentioning
confidence: 99%
“…Reports on the existence of Chn and low sulfated CS are limited. These substrates have been found in human plasma and urine (29), the dried regurgitated saliva of male Collocalia swiftlets (30), squid skin (31), the fruit fly Drosophila melanogaster (32), and the developing nematocyst of Hydra magnipapillata (33). Their physiological significance may be revealed by analyses using Chnase.…”
mentioning
confidence: 99%